2021
DOI: 10.1097/mpg.0000000000003091
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is a Predictor for Adverse Clinical Outcome in Pediatric Inflammatory Bowel Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…First, 110 patients with IBD were included in the study cohort, which is more than in previous studies (36)(37)(38). Second, this study used the AWGS2019 criteria to diagnose sarcopenia, which is novel, as few studies of sarcopenia have used this approach (36)(37)(38)(39)(40). Third, this study also found that low BMI and low Alb levels were risk factors for developing sarcopenia.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…First, 110 patients with IBD were included in the study cohort, which is more than in previous studies (36)(37)(38). Second, this study used the AWGS2019 criteria to diagnose sarcopenia, which is novel, as few studies of sarcopenia have used this approach (36)(37)(38)(39)(40). Third, this study also found that low BMI and low Alb levels were risk factors for developing sarcopenia.…”
Section: Discussionmentioning
confidence: 80%
“…This study had several advantages. First, 110 patients with IBD were included in the study cohort, which is more than in previous studies (36)(37)(38). Second, this study used the AWGS2019 criteria to diagnose sarcopenia, which is novel, as few studies of sarcopenia have used this approach (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous reports that sarcopenia is a poor prognostic factor in patients with IBD undergoing surgery [ 19 , 26 , 27 , 30 , 31 , 54 , 81 , 82 , 83 , 84 , 85 , 86 ]. There are also reports that sarcopenia correlates with the severity of IBD [ 31 , 80 ]. There are reports that sarcopenia is helpful in determining treatment decisions for patients with IBD [ 23 ], that skeletal muscle adiposity is associated with prolonged hospitalization and rehospitalization in patients with IBD [ 83 ], and that sarcopenia is associated with osteoporosis in patients with IBD [ 87 ].…”
Section: Prognostic Impact Of Sarcopenia In Patients With Ibdmentioning
confidence: 99%
“…Table 2 shows reports on the relationship between sarcopenia and prognoses in patients with IBD [19,23,26,27,[30][31][32]54,[80][81][82][83][84][85][86][87]. There have been numerous reports that sarcopenia is a poor prognostic factor in patients with IBD undergoing surgery [19,26,27,30,31,54,[81][82][83][84][85][86].…”
Section: Prognostic Impact Of Sarcopenia In Patients With Ibdmentioning
confidence: 99%
“…Sarcopenia due to malnutrition has emerged as an important problem for CD patients. 16 17 18 There have been efforts made to quantify the body composition of CD patients using the psoas muscle area on routine MRI. 19 In our study, psoas muscle thickness was significantly lower in CD patients on initial abdominal CT (19.2 mm vs. 22 mm, p =0.040).…”
Section: Discussionmentioning
confidence: 99%